Strengthening the pastor's soul developing personal authenticity for pastoral effectiveness - Ezell, Rick (Grand Rapids, MI Kregel, 1995)
Includes bibliographical references.
Reprint. Originally published as : "Ministry on the cutting edge".
Keywords: Pastoral theology